PENGARUH WORK OVERLOAD, AMBIGUITAS PERAN DAN BUDAYA ORGANISASI TERHADAP STRES KERJA - Satrini, I Dewa Ayu Kadek; Riana, I Gede; Subudi, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of research is to analyze the influence of work overload, role ambiguity and organization culture  against job stres employees BPS Province of Bali. BPS Bali includes 10 work units that 9 units of district(city) and one work unit BPS Province. A study population of as many as 274 respondents. The sampling technique using a Krejcie Table  with an error rate of 5% yield samples are 159 respondents. Kind of causality and research including research with survey method and data collection via questionnaires. The results of data analysis showed that partial work overload, the ambiguities of roles and organizational culture affects to job stress.
Keywords: work overload, ambiguities of role, organizational culture and job stres